(untitled) (European Journal of Pure and Applied Mathematics, 2023)
\( ewcommand orm[1]#1Vert ewcommand ormx[1]#1 \)In this paper several tensorial norm inequalities for continuous functions of selfadjoint operators in Hilbert spaces have been obtained. Multiple inequalities are obtained with variations due to the convexity properties of the mapping f orm(1B-A1)^-1[exp(1B)-exp(A1)]- exp(A1+1B2) orm1B-A1^2 ormf’’_I,+∞ 24.